Physical activity recommendations from general practitioners in Australia. Results from a national survey - Short, C.; Hayman, M.; Rebar, Amanda; Gunn, K.; De Cocker, K.; Duncan, M.; Turnbull, D.; Dollman, J.; Van Uffelen, J.; Vandelanotte, C. (Wiley-Blackwell Publishing Asia, 2016)
© 2015 Public Health Association of Australia. Objective: To identify subgroups of Australian adults likely to receive physical activity advice from their general practitioner and to evaluate the content of the advice provided. Methods: Participants (n=1,799), recruited from the Australian Health and Social Science panel, completed an online survey. Signal Detection Analysis was used to identify subgroups that were more/less likely to have received physical activity recommendations. Results: Overall, 18% of participants received a physical activity recommendation from their general practitioner in the past 12 months and eight unique subgroups were identified. The subgroup with the highest proportion (54%) of participants reporting that they received a physical activity recommendation was those with poor physical and mental health-related quality of life and an average daily sitting time of <11 hours. Other subgroups with high proportions of individuals receiving recommendations were characterised by higher weight and/or the presence of co-morbidities. The most commonly prescribed physical activity type was aerobic activity. Few participants received specific physical activity advice. Conclusions: General practitioners are incorporating physical activity promotion into their practice, but primarily as a disease management tool and with limited specificity. Implications: Strategies to assist Australian general practitioners to effectively promote physical activity are needed.